Classic : an it girl novel - Von Ziegesar, Cecily (It girl, 2010)
Each year at Valentine's Day, the Waverly Academy Computer Society runs Perfect Match, an online personality survey that pairs up Waverly Owls with their supposed soul mates. Now the campus is overrun with peculiar pairings, odd couples, and mischief-makers hoping to play Cupid for a day.